Conocimiento y prácticas de medidas preventivas sobreleptospirosis en pobladores adultos del asentamiento humano Amador Bartens de Moronacocha Iquitos 2022 - Arévalo Huamán, Raquel Amparo (2023)
The problem studied was the following: ¿Is there a relationship between the level of knowledge and practice of preventive measures on Leptospirosis in adult residents from 18 to 60 years of age of both sexes of the Amador Bartens de Moronacocha Human Settlement, Iquitos 2022? The objective was to determine the relationship between the level of knowledge and practice of preventive measures on Leptospirosis. Quantitative study with nonexperimental, correlational design, the sample was 60 residents. Observation, interview and home visit were the techniques used in the study, while the instruments were the Leptospirosis knowledge questionnaire, which had 98.5% validity and 95.9% reliability, and the checklist. of practices of preventive measures which had a validity of 98.0% and reliability of 96.5%. The study determined in knowledge about Leptospirosis 66.7% low, 20.0% medium and 13.3% high, in practices of preventive measures of Leptospirosis 75.0% carried out bad practices, and 25.0% good practices, it was obtained (X 2 = 8.578; p = 0.014; gl = 2; α = 0.05; and 95% confidence level). The work concluded that there is a significant relationship between the knowledge and practice of preventive measures on Leptospirosis in adult residents from 18 to 60 years of age of both sexes of the Amador Bartens de Moronacocha Human Settlement in the city of Iquitos, in the year 2022.